The Legal Position of Electronic Stamp Duty According to Law Number 10 of 20201 Concerning Stamp Duty - Karman Karman; Sriono Sriono; Abdul Hakim (International Journal Labs, 2023)
In Indonesia itself, in making transactions or agreements in general we use seals. We usually find seals on a document or securities. This study aims to find out and analyze the legal position of electronic seals according to law number 10 of 20201 concerning stamp duty. As well as analyzing the repayment of stamp duty on documents in Indonesia associated with the development of information technology in Indonesia. This research belongs to the normative type of research. So it can be known that the legal force of this Electronic Seal is the same as that of the sticky seal. Furthermore, the payment of stamp duty on documents in Indonesia is associated with the development of information technology in Indonesia has actually experienced significant development since the enactment of the Stamp Duty Law in 1986.